Species-specific impact of microplastics on coral physiology. (15th January 2021) - Mendrik, F.M.; Henry, T.B.; Burdett, H.; Hackney, C.R.; Waller, C.; Parsons, D.R.; Hennige, S.J.
Abstract: There is evidence that microplastic (MP) pollution can negatively influence coral health; however, mechanisms are unknown and most studies have used MP exposure concentrations that are considerably higher than current environmental conditions. Furthermore, whether MP exposure influences coral susceptibility to other stressors such as ocean warming is unknown. Our objective was to determine the physiology response of corals exposed to MP concentrations that have been observed in-situ at ambient and elevated temperature that replicates ocean warming. Here, two sets of short-term experiments were conducted at ambient and elevated temperature, exposing the corals Acropora sp. and Seriatopora hystrix to microspheres and microfibres. Throughout the experiments, gross photosynthesis and net respiration was quantified using a 4-chamber coral respirometer, and photosynthetic yields of photosystem II were measured using Pulse-Amplitude Modulated (PAM) fluorometry. Results indicate the effect of MP exposure is dependent on MP type, coral species, and temperature. MP fibres (but not spheres) reduced photosynthetic capability of Acropora sp., with a 41% decrease in photochemical efficiency at ambient temperature over 12 days. No additional stress response was observed at elevated temperature; photosynthetic performance significantly increased in Seriatopora hystrix exposed to MP spheres. These findings show that a disruption to coral photosynthetic ability can occur at MP concentrations that have been observed in the marine environment and that MP pollution impact on corals remains an important aspect for further research. Graphical abstract: Image 1 Highlights: Corals were exposed to microplastic types at ambient and elevated temperatures. Gross photosynthesis, net respiration, and photosynthetic yields were assessed. Responses were species, microplastic type, and temperature dependent. Fibres decreased photosynthetic ability for Acropora sp. No stress response occurred at elevated temperature for either species.